Status Of Soil Chemical Properties in Cocoa (Theobroma cacao) Plantation Land in Lanona Village, Bungku Tengah District, Morowali Regency, Central Sulawesi - Nadine Sandra Agustina; Epriani Rimbun; Iskandar; Hasnia (International Journal of Technology and Education Research, 2026)
Cocoa (Theobroma cacao) is a major plantation commodity in Lanona Village, Bungku Tengah District, Morowali Regency, yet its productivity remains low, partly because the chemical fertility status of the local soils has not been documented. This study aimed to determine the status of soil chemical properties (pH, organic carbon, total N, and total P) in cocoa plantation land in Lanona Village according to slope position and soil depth. A soil survey was carried out at three slope positions (footslope, midslope, and summit) and two depths (0–20 cm and 20–40 cm), with three replicates for each combination, yielding 18 soil samples. Soil pH ranged from acidic to neutral (5.22–7.15), with the highest values at the midslope and the lowest at the summit. Organic carbon content was moderate to high (2.26–4.60%), highest at the midslope and decreasing with depth. Total N was low to moderate (0.11–0.28%), whereas total P varied widely (2.78–25.02 ppm), with a very high status found only at the midslope. Slope position, together with base leaching and organic matter accumulation, was the main factor controlling the observed variation in soil chemical properties. The midslope showed the chemical fertility status most favourable for cocoa cultivation, whereas the footslope and summit required improvement, particularly through dolomitic liming, organic matter addition, and more targeted N and P fertilisation.